2016
DOI: 10.1016/j.riem.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Intervención educativa sobre el nivel de conocimientos en pacientes con diabetes y baja o nula escolaridad

Abstract: Objetivo: Evaluar una intervención integral de educación en diabetes sobre el nivel de conocimientos en pacientes con dicha enfermedad. Método: Diseño cuasiexperimental con 17 pacientes diagnosticados de diabetes que refirieron ser analfabetos o contar con una educación básica y pertenecer a la comunidad Villa Aquiles Serdán, Pachuca, Hidalgo. Entre julio y diciembre de 2013, se aplicó una encuesta para identificar sexo, edad, escolaridad, ocupación, estado civil y tiempo de evolución, y solicitamos la m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Nurses work with PLDM to provide information through health education to achieve good adherence with pharmacological and nonpharmacological clinical management strategies (Castro-Meza et al, 2017;Dios-Guerra & Pérula de Torres, 2012;Hevia, 2016;López-López, Ortiz-Gress, & López-Carbajal, 2016;Solano-Solano et al, 2013). Although research has focused on the delivery of information to reinforce healthy behaviors, few studies point to the importance of the nursepatient relationship in strengthening self-esteem and the development of personal strategies to address psychological wellbeing (Dios-Guerra & Pérula de Torres, 2012;Hevia, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Nurses work with PLDM to provide information through health education to achieve good adherence with pharmacological and nonpharmacological clinical management strategies (Castro-Meza et al, 2017;Dios-Guerra & Pérula de Torres, 2012;Hevia, 2016;López-López, Ortiz-Gress, & López-Carbajal, 2016;Solano-Solano et al, 2013). Although research has focused on the delivery of information to reinforce healthy behaviors, few studies point to the importance of the nursepatient relationship in strengthening self-esteem and the development of personal strategies to address psychological wellbeing (Dios-Guerra & Pérula de Torres, 2012;Hevia, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The average age and years of diabetes mellitus being diagnosed was 55.7 and 6.07 respectively. Lopez L and associates showed similar data, in which the average age was 52.6 ± 5.8 years and the average years with diabetes mellitus was 112.00 (9.3 years) [12]. In contrast, in a study done by Alonso F the average age was 68.9 years [14].…”
Section: Discussionmentioning
confidence: 68%
“…Therefore, in this study we aimed to determine the self-awareness about self-care of the feet in the 360 patients with diabetes mellitus type 2 who met the inclusion criteria. The results showed a higher incidence in the female gender with 55.8%, other studies confirmed this higher incidence in the female gender with a 64.7% of women with this entity [12]. On the other hand, in a study done in northwest Ethiopia, the male gender showed a higher incidence of 55.2% compared to the female gender with 44.8% [13].…”
Section: Discussionmentioning
confidence: 78%
“…Nevertheless, basic knowledge and the necessary motivation are not always available to carry out these self-care behaviors. 8,9 Selfcare refers to the actions that people adopt for the benefit of their own health, without formal medical supervision. The role of the active patient provides a double benefit: it acquires autonomy with respect to the system and, in turn, helps to reduce unnecessary demand on the health system.…”
Section: Casual Glucosementioning
confidence: 99%